Fatigue model of domestic 316LN steel in simulated primary coolant environment of CAP1400. (January 2020) - Zhong, Weihua; Qian, Guian; Tong, Zhenfeng; Wu, Wenwang; Zhu, Shun-Peng; Wang, Chenglong
Highlights: Fatigue tests of domestic 316LN carried out in simulated primary coolant environment. Effect of temperature, strain rate and dissolved oxygen on fatigue life analysed. Fatigue model developed. Fatigue model more accurate in lifetime prediction. Abstract: Fatigue tests of domestic 316LN were carried out in the simulated primary coolant environment of CAP1400 (the advanced 3rd generation nuclear power plants developed in China). Effects of temperature, strain rate and dissolved oxygen (DO) on fatigue life were analyzed. Based on the results, a fatigue model was developed. Fatigue life in primary coolant environment increases logarithmically as the temperature decreases from 321 ℃ to 150 ℃. When the temperature decreases to 150 ℃, fatigue life in primary coolant environment is very close to that in air environment. Fatigue life increases as the strain rate increases from 0.004%/s to 1%/s. After the strain increases to more than 0.4%/s, fatigue life in primary coolant environment is very close to that in air environment. Effect of DO on fatigue life in primary coolant environment is not obvious in the DO range of 0.005 ppm to 8 ppm. Compared with NUREG6909 model, the present fatigue model is more accurate in lifetime prediction of domestic 316LN.